Ultra-Wideband Radio Technologies for Communications, Localization and Sensor Applications - Thomä, Reiner; Knöchel, Reinhard H.; Sachs, Jürgen; Willms, Ingolf; Zwick, Thomas (IntechOpen, 2013)
Ultra-Wideband Radio (UWB) earmarks a new radio access philosophy and exploits several GHz of bandwidth. It promises high data rate communication over short distances as well as innovative radar sensing and localization applications with unprecedented resolution. Fields of application may be found, among others, in industry, civil engineering, surveillance and exploration, for security and safety measures, and even for medicine. The book considers the basics and algorithms as well as hardware and application issues in the field of UWB radio technology for communications, localization and sensing based on the outcome of DFG's priority-funding program "Ultra-Wideband Radio Technologies for Communications, Localization and Sensor Applications (UKoLoS)".